miRNA–protein–metabolite interaction network reveals the regulatory network and players of pregnancy regulation in dairy cows - Chatterjee, Bhaswati; Thakur, Suman S. (Frontiers in Cell and Developmental Biology, 2024)
Pregnancy is a complex process involving complex molecular interaction networks, such as between miRNA–protein, protein–protein, metabolite–metabolite, and protein–metabolite interactions. Advances in technology have led to the identification of many pregnancy-associated microRNA (miRNA), protein, and metabolite fingerprints in dairy cows. An array of miRNA, protein, and metabolite fingerprints produced during the early pregnancy of dairy cows were described. We have found the in silico interaction networks between miRNA–protein, protein–protein, metabolite–metabolite, and protein–metabolite. We have manually constructed miRNA–protein–metabolite interaction networks such as bta-miR-423-3p–IGFBP2–PGF2α interactomes. This interactome is obtained by manually combining the interaction network formed between bta-miR-423-3p–IGFBP2 and the interaction network between IGFBP2–PGF2α with IGFBP2 as a common interactor with bta-miR-423-3p and PGF2α with the provided sources of evidence. The interaction between bta-miR-423-3p and IGFBP2 has many sources of evidence including a high miRanda score of 169, minimum free energy (MFE) score of −25.14, binding probability (p) of 1, and energy of −25.5. The interaction between IGFBP2 and PGF2α occurs at high confidence scores (≥0.7 or 70%). Interestingly, PGF2α is also found to interact with different metabolites, such as PGF2α–PGD2, PGF2α–thromboxane B2, PGF2α–PGE2, and PGF2α–6-keto-PGF1α at high confidence scores (≥0.7 or 70%). Furthermore, the interactions between C3–PGE2, C3–PGD2, PGE2–PGD2, PGD2–thromboxane B2, PGE2–thromboxane B2, 6-keto-PGF1α–thromboxane B2, and PGE2–6-keto-PGF1α were also obtained at high confidence scores (≥0.7 or 70%). Therefore, we propose that miRNA–protein–metabolite interactomes involving miRNA, protein, and metabolite fingerprints of early pregnancy of dairy cows such as bta-miR-423-3p, IGFBP2, PGF2α, PGD2, C3, PGE2, 6-keto-PGF1 alpha, and thromboxane B2 may form the key regulatory networks and players of pregnancy regulation in dairy cows. This is the first study involving miRNA–protein–metabolite interactomes obtained in the early pregnancy stage of dairy cows.